Perwalian anak perempuan dalam Islam: Antara otoritas ayah dan hak perempuan - Rifai, Ahmad (Maliki Interdisciplinary Journal, 2024)
This paper discusses the guardianship of girls in Islam and women’s rights. The method used to write this essay is desk research. The majority of jurists in Indonesia adhere to the Shafi’i school of thought and the marriage of a woman who marries without a guardian is considered invalid. For a woman who does not have a guardian in marriage, her guardian is the wali of the court. Guardianship of daughters in Islam is a complex and highly controversial issue. On the one hand, there is the authority of the father as wali nikah and wise guardian over his daughter. On the other hand, there is also the woman’s right of self-determination, including with regard to marriage. This journal aims to analyze the guardianship of daughters in Islam, taking into account the father’s authority and the woman’s rights.